HUBUNGAN HUKUM YANG MENIMBULKAN HAK DAN KEWAJIBAN DALAM KONTRAK BISNIS - HARYANTO, TOTOK DWINUR (Wacana Hukum, 2010)
Abstract: All commercial activities that consist of production, distribution and trading of goods and services to gain the profit should be declared in a contract to give guarantee and assurance to all sides. In the case that there is a conflict, this contract will help them to solve the problem. Keywords: business contract, right and obligation.